From insect endosymbiont to phloem colonizer: comparative genomics unveils the lifestyle transition of phytopathogenic Arsenophonus strains - Mathieu Mahillon; Christophe Debonneville; Raphaël Groux; David Roquis; Justine Brodard; Franco Faoro; Xavier Foissac; Olivier Schumpp; Jessica Dittmer (mSystems)
ABSTRACT Bacteria infecting the plant phloem represent a growing threat worldwide. While these organisms often resist in vitro culture, they multiply both in plant sieve elements and hemipteran vectors. Such cross-kingdom parasitic lifestyle has emerged in diverse taxa via distinct ecological routes. In the genus Arsenophonus, the phloem pathogens “Candidatus Arsenophonus phytopathogenicus” (Ap) and “Ca. Phlomobacter fragariae” (Pf) have evolved from insect endosymbionts, but the genetic mechanisms underlying this transition have not been explored. To fill this gap, we obtained the genomes of both strains from insect host metagenomes. The resulting assemblies are highly similar in size and functional repertoire, rich in viral sequences, and closely resemble the genomes of several facultative endosymbiotic Arsenophonus strains of sap-sucking hemipterans. However, a phylogenomic analysis demonstrated distinct origins, as Ap belongs to the “Triatominarum” clade, whereas Pf represents a distant species. We identified a set of orthologs encoded only by Ap and Pf in the genus, including hydrolytic enzymes likely targeting plant substrates. In particular, both bacteria encode putative plant cell wall-degrading enzymes and cysteine peptidases related to xylellain, a papain-like peptidase from Xylella fastidiosa, for which close homologs are found in diverse Pseudomonadota infecting the plant vasculature. In silico predictions and gene expression analyses further support a role during phloem colonization for several of the shared orthologs. We conclude that the double emergence of phytopathogenicity in Arsenophonus may have been mediated by a few horizontal gene transfer events, involving genes acquired from other Pseudomonadota, including phytopathogens.IMPORTANCEWe investigate the genetic mechanisms of a transition in bacterial lifestyle. We focus on two phloem pathogens belonging to the genus Arsenophonus: “Candidatus Arsenophonus phytopathogenicus” and “Ca. Phlomobacter fragariae.” Both bacteria cause economically significant pathologies, and they have likely emerged among facultative insect endosymbionts. Our genomic analyses show that both strains are highly similar to other strains of the genus associated with sap-sucking hemipterans, suggesting a recent lifestyle shift. Importantly, although the phytopathogenic Arsenophonus strains belong to distant clades, they share a small set of orthologs unique in the genus pangenome. We provide evidence that several of these genes produce hydrolytic enzymes that are secreted and may target plant substrates. The acquisition and exchange of these genes may thus have played a pivotal role in the lifestyle transition of the phytopathogenic Arsenophonus strains.